Superior migration ability of umbilical cord-derived mesenchymal stromal cells (MSCs) toward activated lymphocytes in comparison with those of bone marrow and adipose-derived MSCs - Hori, Akiko; Takahashi, Atsuko; Miharu, Yuta; Yamaguchi, Satoru; Sugita, Masatoshi; Mukai, Takeo; Nagamura, Fumitaka; Nagamura-Inoue, Tokiko (Frontiers in Cell and Developmental Biology, 2024)
Introduction: Mesenchymal stromal cells (MSCs) are activated upon inflammation and/or tissue damage and migrate to suppress inflammation and repair tissues. Migration is the first important step for MSCs to become functional; however, the migration potency of umbilical cord-derived MSCs (UC-MSCs) remains poorly understood. Thus, we aimed to assess the migration potency of UC-MSCs in comparison with those of bone marrow-derived MSCs (BM-MSCs) and adipose tissuederived MSCs (AD-MSCs) and investigate the influence of chemotactic factors on the migration of these cells. Methods: We compared the migration potencies of UC-, BM-, and AD-MSCs toward allogeneic stimulated mononuclear cells (MNCs) in mixed lymphocyte reaction (MLR). The number of MSCs in the upper chamber that migrated toward the MLR in the lower chamber was counted using transwell migration assay. Results and Discussion: UC-MSCs showed significantly faster and higher proliferation potencies and higher migration potency toward unstimulated MNCs and MLR than BM-and AD-MSCs, although the migration potencies of the three types of MSCs were comparable when cultured in the presence of fetal bovine serum. The amounts of CCL2, CCL7, and CXCL2 in the supernatants were significantly higher in UC-MSCs co-cultured with MLR than in MLR alone and in BM-and AD-MSCs co-cultured with MLR, although they did not induce the autologous migration of UC-MSCs. The amount of CCL8 was higher in BM-and AD-MSCs than in UC-MSCs, and the amount of IP-10 was higher in AD-MSCs co-cultured with MLR than in UC-and BM-MSCs. The migration of UC-MSCs toward the MLR was partially attenuated by platelet-derived growth factor, insulin-like growth factor 1, and matrix metalloproteinase inhibitors in a dosedependent manner. Conclusion: UC-MSCs showed faster proliferation and higher migration potency toward activated or non-activated lymphocytes than BM-and AD-MSCs. The functional chemotactic factors may vary among MSCs derived from different tissue sources, although the roles of specific chemokines in the different sources of MSCs remain to be resolved.